2020
DOI: 10.3389/fnins.2020.577937
|View full text |Cite
|
Sign up to set email alerts
|

FFA-DMRI: A Network Based on Feature Fusion and Attention Mechanism for Brain MRI Denoising

Abstract: Magnetic Resonance Imaging (MRI) is an indispensable tool in the diagnosis of brain diseases due to painlessness and safety. Nevertheless, Rician noise is inevitably injected during the image acquisition process, which leads to poor observation and interferes with the treatment. Owing to the complexity of Rician noise, using the elimination method of Gaussian to remove it does not perform well. Therefore, the feature fusion and attention network (FFA-DMRI) is proposed to separate noise from observed MRI. Inspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In an application to imaging prostate, Hong et al presented a Bayes shrinkage-based fused wavelet transform (BSbFWT) and Block-based autoencoder network (BBAuto-Net) for removal of noise from prostate MR images [ 121 ]. The method was tested on prostate mp-MRI data obtained from 1.5-T general electric (GE) and 3.0-T Siemens scanners with promising results obtained in comparison with conventional filters such as anisotropic, bilateral, Gabor, Gaussian, mean, NLM, wavelet, Wiener, autoencoders, and autoencoders with NLM filters.…”
Section: Noise Reduction In Mrimentioning
confidence: 99%
“…In an application to imaging prostate, Hong et al presented a Bayes shrinkage-based fused wavelet transform (BSbFWT) and Block-based autoencoder network (BBAuto-Net) for removal of noise from prostate MR images [ 121 ]. The method was tested on prostate mp-MRI data obtained from 1.5-T general electric (GE) and 3.0-T Siemens scanners with promising results obtained in comparison with conventional filters such as anisotropic, bilateral, Gabor, Gaussian, mean, NLM, wavelet, Wiener, autoencoders, and autoencoders with NLM filters.…”
Section: Noise Reduction In Mrimentioning
confidence: 99%
“…Hong, et al [50] proposed an attention mechanism-based convolutional neural network for MRI denoising. They also applied the feature fusion technique by combining the local features with the global ones to boost the network's capacity.…”
Section: mentioning
confidence: 99%
“…In [ 26 ], Ran et al suggested a residual encoder-decoder Wasserstein generated countermeasure network (RED-WGAN) for MR image denoising. Hong et al designed a spatial attention mechanism to obtain the area of interest in MR images, which made use of the multilevel structure and boosted the expressive ability of the network [ 27 ]. Tripathi and Bag proposed a novel CNN for MR image denoising.…”
Section: Introductionmentioning
confidence: 99%